Model-based assembly management in machine tool manufacturing - Andreas Drexl; Rainer Kolisch (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
In machine tool assembly several make-to-order products have to be manufactured simultaneously in a multi-stage production system. Due to customer requirements batches are very small. A process plan specifies the neccessary machines, tools, auxiliary devices as well as the operations to be performed. We consider the small batch machine tool assembly problem with alternative process plans and multiple resource-constraints. This problem basically relates to nonpreemptive multi-mode resource-constrained project scheduling. Two models, each with a related class of methods, are considered to be most important. The first minimizes the makespan with respect to precedence constraints and a given set of renewable resources. It is desgined for (a-) periodic (re-) scheduling as well as to help the decision maker in determining appropriate schedules with associated release dates and deadlines for machine tool orders in acquisition. The second, a new type of model, minimizes renewable resources required in addition to the available stock in order to satisfy deadlines. Among other purposes, it should help to deal with several kinds of interferences (machine breakdowns, etc.). Beyond these scheduling components the system provides an ordering component as well as a layout component.
Keywords: 650; Machine tool manufacturing; assembly of small batches; project scheduling models; layout component; ordering component; leitstand; Produktionssteuerung; Werkzeugmaschine; Theorie